STRES KERJA PADA TUNA NETRA YANG BEKERJA SEBAGAI KARYAWAN PERUSAHAAN BERBASIS PROFIT DI JAKARTA - Asrini Mahdia (Jurnal Psikologi, 2014)
We have had many companies profit in Jakarta, which launched an inclusive program is to employ blind people in the field who usually employ berfisik normal. Usually companies will choose division customer relations job description so far is still affordable by the accessibility of the blind. This study aims to determine the occupational stress experienced by visually impaired employees who work in an inclusive environment that profit companies tend to have a high competitive atmosphere and designed to physically less accessible by disabled employees. This study used a qualitative phenomenological method with data collection through interviews and observations. The results of this study indicate that the majority of subjects had increased work stress due to the persistence of the problems in the relationship between employee relations, and the impact on the working climate because of its negative relationship between employee relations. But overall subject themselves psychologically capable mencoping so it is not too intrusive work processes subject.Keywords: Job stress, Blind, Employees, Profit-based company